2002
DOI: 10.1086/341895
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis and International Travel

Abstract: Infection with Schistosoma species is acquired by exposure to fresh water that harbors cercariae released by infected snails. Although the route of infection is clear, clinical presentation of the established infection in the nonimmune tourist typically differs from that in the local population of areas of endemicity. For the health care practitioner, the traveler's syndrome presents distinctive management problems: water-transmitted bacterial and viral infections may coexist, and identification of the stage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
72
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 23 publications
1
72
0
2
Order By: Relevance
“…This medicine is effective to eliminate adult worms in the initial phase (5-6 weeks) in S. mansoni and S. japonicum, as well as 10-12 weeks in S. haematobium, but not for its schistosomulae. 9 The reccomended dose for Praziquantel is 40 mg/kgBW single dose, or 50 mg/kgBW in S. japonicum infections. 9 A newer study showed that anti-malarial medicine like artemisinin, mefloquine, and trioxolane derivate, can also be used as antischistosoma.…”
Section: How Is the Management Of Schistosomiasis?mentioning
confidence: 99%
See 4 more Smart Citations
“…This medicine is effective to eliminate adult worms in the initial phase (5-6 weeks) in S. mansoni and S. japonicum, as well as 10-12 weeks in S. haematobium, but not for its schistosomulae. 9 The reccomended dose for Praziquantel is 40 mg/kgBW single dose, or 50 mg/kgBW in S. japonicum infections. 9 A newer study showed that anti-malarial medicine like artemisinin, mefloquine, and trioxolane derivate, can also be used as antischistosoma.…”
Section: How Is the Management Of Schistosomiasis?mentioning
confidence: 99%
“…9 The reccomended dose for Praziquantel is 40 mg/kgBW single dose, or 50 mg/kgBW in S. japonicum infections. 9 A newer study showed that anti-malarial medicine like artemisinin, mefloquine, and trioxolane derivate, can also be used as antischistosoma. Thesse medicine will be more effective in combination with Praziquantel.…”
Section: How Is the Management Of Schistosomiasis?mentioning
confidence: 99%
See 3 more Smart Citations